Pentingnya Mencari Ilmu dan Ketaatan Berdasarkan Perspektif Religiusitas Dalam Serat Sejarah Aspiyah - Rendy Dwi Saputra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This article discusses the importance of seeking knowledge and also obedience based on the perspective of religiosity in the historical fiber of aspiyah. This study uses descriptive qualitative research methods, and by using a functionalism approach aims to build a social system or social structure obtained from the study of patterns of functioning relationships between individuals, between groups, or between social institutions that exist in a society. The results of this study are about how to seek knowledge, the stages in the process of seeking knowledge, ethics in gaining knowledge and also obedience in knowledge so as to obtain knowledge that is useful in a learning process and is also strengthened by hadith and the Koran, as well as existing quotes. in the historical fiber of aspiyah.